1984
DOI: 10.1139/m84-088
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence homologies of unique DNA's of some cultivated and wild mushrooms

Abstract: The unique sequence DNA's of several wild and cultivated fungi including Agaricus brunnescens (=Agaricus bisporus), Agaricus bitorquis, Amanita muscaria, Amanita phalloides, Pleurotus ostreatus, Lentinus edodes, and Schizophyllum commune were compared by DNA–DNA hybridization. In addition, the characterization of a number of fungal DNA's are reported for the first time. Unique sequence DNA from Agaricus brunnescens and P. ostreatus was labeled by nick translation and each was hybridized with an excess of unlab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Consistent with our results, other studies have reported extensive genetic differentiation between diverging fungal species (Bicknell and Douglas 1970;Horgen et al 1984;Vilgalys and Johnson 1987;Dettman et al 2003). The high amount of genetic diversity observed between relatively recently separated species suggests that speciation in Mycosphaerella was not only associated with host adaptation but was also accompanied by significant genetic differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, other studies have reported extensive genetic differentiation between diverging fungal species (Bicknell and Douglas 1970;Horgen et al 1984;Vilgalys and Johnson 1987;Dettman et al 2003). The high amount of genetic diversity observed between relatively recently separated species suggests that speciation in Mycosphaerella was not only associated with host adaptation but was also accompanied by significant genetic differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The genomic complexity of only a few fungi has been studied so far [17][18][19][20][21][22][23][24][25][26]. It is clear that the kinetic complexity of single copy DNA and the content of repetitive DNA in P. funiculosum compare well with the corresponding values reported in the literature (Table 3).…”
Section: Discussionmentioning
confidence: 67%
“…All the isolates had specific RFLP patterns and presented a high molecular polymorphism (with the sole exception of P. abalonus) comparable to the polymorphism evidenced by isozyme analysis (Zervakis & Labarere, 1992; Iraçabal & Labrère, 1993; Zervakis et al, 1994). In comparison with the DNA polymorphism of species of the order Agaricales previously described in the genera Armillaria (Anderson et al, 1987), Agaricus (Horgen et al, 1984; Hintz et al, 1989), L,accaria (Armstrong et al, 1989; Gardes et al, 1990) and Lentinus (Kulkarni, 1991), the rDNA polymorphism evidenced in the Pleurotus genus is higher. This could be attributed (i) to the efficiency of the probe used which was a part of the P. cornucopiae rDNA unit mainly constituted by intergenic sequences and (ii) to the loss or creation of new restriction sites and/or of length mutations as already evidenced in P. cornucopiae rDNA (Iraçabal & Labrère, 1994).…”
Section: Discussionmentioning
confidence: 69%